Complete mitochondrial genome of the brain coral Platygyra daedalea (Ellis & Solander, 1786) - Xinyao Chang; Xiaomei Chen; Shaowen Ke; Xing Li; Kai Chen; Yuli Li; Lisui Bao; Jingjie Hu; Shi Wang; Zhenmin Bao (Mitochondrial DNA. Part B. Resources)
Platygyra daedalea Ellis & Solander, 1786, is a dominant species within the world’s warmest reefs, making it a critical model for investigating coral stress resistance and adaptive evolutionary mechanisms. This study presents the first sequenced and annotated mitogenome of the reef-building coral P. daedalea. The mitogenome is 16,363 bp in length, containing 13 protein-coding genes, two ribosomal RNA genes, and two transfer RNA genes. The base composition is 24.8% adenine (A), 13% cytosine (C), 20.4% guanine (G), and 41.8% thymine (T), with a G-C content of 33.4%. We conducted a comparative analysis between P. daedalea and P. carnosa. Notably, genetic variations in the ND5 and COXI genes emerge as potential markers for distinguishing species within the Platygyra genus. Additionally, the protein-coding gene ND6 has been subjected to strong selective pressure. Phylogenetic analysis based on the complete mitogenome aligns with the internal clade structure of Scleractinia reported in previous studies, reinforcing the evolutionary insights provided by this dataset.